The Seduction Script: Psychological and Cultural Norms of Interpersonal Approaches As Markers for Sexual Aggression and Abuse - Landgraf, Steffen; von Treskow, Isabella (Frontiers in Psychology, 2017)
Hardly any subjects enjoy greater – public or private – interest than the art of flirtation and seduction. However, interpersonal approach behavior not only paves the way for sexual interaction and reproduction, but it simultaneously integrates non-sexual psychobiological and cultural standards regarding consensus and social norms. In the present paper, we use script theory as a concept that extends across psychological and cultural science to assess behavioral options during interpersonal approaches. Specifically, we argue that approaches follow scripted event sequences that entail ambivalence as an essential communicative element. On the one hand, ambivalence may facilitate interpersonal approaches by maintaining and provoking situational uncertainty, so that the outcome of an action – even after several approaches and dates – remains ambiguous. On the other hand, ambivalence may increase the risk for sexual aggression or abuse, depending on the individual’s abilities, the circumstances, and the intentions of the interacting partners. Recognizing latent sequences of sexually aggressive behavior, in terms of their rigid structure and behavioral options, may thus enable individuals to use resources efficiently, avoid danger, and extricate themselves from assault situations. We conclude that interdisciplinary script knowledge about ambivalence as a core component of the seduction script may be helpful for counteracting subtly aggressive intentions and preventing sexual abuse. We discuss this with regard to the nature-nurture debate as well as phylogenetic and ontogenetic aspects of interpersonal approach behavior and its medial implementation.